2011
DOI: 10.1073/pnas.1101379108
|View full text |Cite
|
Sign up to set email alerts
|

Selective activation of the transcription factor ATF6 mediates endoplasmic reticulum proliferation triggered by a membrane protein

Abstract: It is well known that the endoplasmic reticulum (ER) is capable of expanding its surface area in response both to cargo load and to increased expression of resident membrane proteins. Although the response to increased cargo load, known as the unfolded protein response (UPR), is well characterized, the mechanism of the response to membrane protein load has been unclear. As a model system to investigate this phenomenon, we have used a HeLa-TetOff cell line inducibly expressing a tail-anchored construct consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 37 publications
3
79
0
Order By: Relevance
“…Table 1 summarizes data obtained for the four manipulations [three exemplar nicotinic ligands and nAChRs containing ␤2 enhanced-ER-export mutant subunits]. All four manipulations suppressed ATF6 translocation, which serves as a key sensor for ER stress and the UPR (Ron and Walter, 2007;Hetz and Glimcher, 2009;Maiuolo et al, 2011), but the only other consistent phenomenon was the increased total Sec24D fluorescence in ERES. Therefore, we suggest that increased ER exit of nAChRs underlies the suppression of ATF6 translocation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes data obtained for the four manipulations [three exemplar nicotinic ligands and nAChRs containing ␤2 enhanced-ER-export mutant subunits]. All four manipulations suppressed ATF6 translocation, which serves as a key sensor for ER stress and the UPR (Ron and Walter, 2007;Hetz and Glimcher, 2009;Maiuolo et al, 2011), but the only other consistent phenomenon was the increased total Sec24D fluorescence in ERES. Therefore, we suggest that increased ER exit of nAChRs underlies the suppression of ATF6 translocation.…”
Section: Discussionmentioning
confidence: 99%
“…at ASPET Journals on May 12, 2018 molpharm.aspetjournals.org ever, the attenuation of ATF6 translocation is sufficient to suppress ER proliferation when expression of a tail-anchored protein is sensed within the lipid bilayer (Maiuolo et al, 2011). Events downstream from Golgi exit are not thought to influence the UPR markedly, and these events varied among the manipulations.…”
Section: Upr Suppressed By Ligand-nachr Interactions In Er 767mentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, direct sensing of lipid perturbation may contribute to activation of ATF6. For example, perturbation of the lipid bilayer of the ER by the expression of a tail-anchored ER membrane protein resulted in the selective activation of ATF6, in the absence of IRE1␣ and PERK activation (and without ER Ca 2ϩ depletion) (42). Conversely, a recent study has demonstrated that saturation of membrane lipids promoted selective IRE1␣ and PERK activation by enhancing dimerization via their transmembrane domains (43).…”
Section: Table 3 Effect Of Ipla 2 ␥ On Ldlr Promoter-luciferase Repormentioning
confidence: 99%
“…21,22 To explore whether VEGF could also activate other ER stress responses, the PERK phosphorylation and ATF6 cleavage were detected. 23,24 Thapsigargin, a well-known ER stress inducer via ER calcium release, was included as a positive control triggering XBP1 splicing, PERK phopshorylation, and ATF6 cleavage in Hela cell ( Figure 1D). Interestingly, VEGF treatment only activated XBP1 splicing but had no effect on PERK phosphorylation or ATF6 cleavage ( Figure 1D).…”
Section: Vegf Transiently Induces Xbp1 Mrna Splicing In Endothelial Cmentioning
confidence: 99%